Membrane-targeted WAVE mediates photoreceptor axon targeting in the absence of the WAVE complex in Drosophila. - Stephan, R.; Gohl, C.; Fleige, A.; Klämbt, C.; Bogdan, S. (Molecular Biology of the Cell, 2011)
A tight spatial-temporal coordination of F-actin dynamics is crucial for a large variety of cellular processes that shape cells. The Abelson interactor (Abi) has a conserved role in Arp2/3-dependent actin polymerization, regulating Wiskott-Aldrich syndrome protein (WASP) and WASP family verprolin-homologous protein (WAVE). In this paper, we report that Abi exerts nonautonomous control of photoreceptor axon targeting in the Drosophila visual system through WAVE. In abi mutants, WAVE is unstable but restored by reexpression of Abi, confirming that Abi controls the integrity of the WAVE complex in vivo. Remarkably, expression of a membrane-tethered WAVE protein rescues the axonal projection defects of abi mutants in the absence of the other subunits of the WAVE complex, whereas cytoplasmic WAVE only slightly affects the abi mutant phenotype. Thus complex formation not only stabilizes WAVE, but also provides further membrane-recruiting signals, resulting in an activation of WAVE.